The significance of veterinary science in the national economy - Harnett, P. (Statistical and Social Inquiry Society of Ireland, 1956)
I propose to go into the economic significance of veterinary science in the Republic of Ireland and to relate the evidence to the year 1954. The most significant figures I have arrived at are derived from the returns on livestock of the Central Statistics Office. As a matter of fact it was only when I came across a copy of the Statistical Abstract some years ago and then went tracing the causes for the differences between one age group of cattle and another in the same and in subsequent years that I began to appreciate the significance of animal disease in the economics of this country and the place of the veterinarian in our economic set up. I will probably be accused a priori of placing undue trust in statistics and statisticians. From my experience they seem to be mistrusted people. I did not trust them either until I got to know them and appreciate within the limits of my understanding the outstanding value of their work compiled with such extreme care. I am happy to declare myself their disciple, and I wish to take this opportunity to express my appreciation of the work of the Central Statistics Office, and my thanks to Dr Geary and his staff for the help given to me on many occasions.
Read before the Society, 2 March 1956
Keywords: Veterinary science; Agricuture productivity; Livestock quality; 314.15